THU0002 SOLVING THE COMPLEX MHC ASSOCIATIONS IN SLE IDENTIFIES SEX-RELATED GENE EFFECTS. (2nd June 2020) - Kamitaki, N.; Handsaker, B.; Morris, D.; Langefeld, C.; Graham, R.; Criswell, L.; Mccarroll, S.; Vyse, T.
Abstract : Background: Genome-wide association analyses reveal that the Major Histocompatibility Complex (MHC) is the site of the strongest association signals in SLE and Sjögren's syndrome. This associations in lupus and Sjögren's syndrome are linked to HLA alleles: HLA-DRB1*03:01 and HLA-DRB1*15:01 (in Europeans). The DRB1*03:01 allele resides on an extended MHC haplotype which includes loss of the complement C4A gene. Whether C4 makes a genetic contribution to SLE/Sjogren's risk has been a long standing issue of contention 1 . In comparison, it has been shown that elevated copy number of C4 is a genetic risk factor for schizophrenia 2 . Objectives: To define the causal MHC genes in SLE/Sjogren's accommodating both structural and highly polymorphic variation. Methods: Use NG sequencing data from across the MHC to generate a panel of variants that inform class III structural variation involving the candidate genes coding complement C4A and C4B as described 2 . To further improve the resolution of the association using transancestral mapping approach in SLE: examining cohorts of European ancestry (from ImmunoChip) and data from the MHC region of an African-American GWAS in SLE. Results: Comparing European and African data, we have shown that the association signals in SLE can be best explained by signals arising from 1) copy number variation of the complement component 4 ( C4 ) genes in the MHC locus (Fig. 1 ) and 2 ) by a shared region in the class II region on the HLA-DRB1*15:01 (in Europeans) and HLA-DRB1*15:03 (in Africans) that likely operates to elevated HLA class II gene expression (Fig. 2 ). The C4 locus generates a 7-fold variation in risk for lupus (95% CI: 5.88-8.61; p <10 -117 in total) and 16-fold variation in risk for Sjögren's syndrome (95% CI: 8.59-30.89; p <10 -23 in total), with C4A protecting more strongly than C4B in both illnesses. In schizophrenia, elevated C4 copy number elevates disease risk, whereas in SLE and Sjögren's lower copy numbers of C4 genes correlate with higher disease risk. In all three illnesses, C4 alleles acted more strongly in men than in women: common combinations of C4A and C4B generated 14-fold variation in risk for lupus and 31-fold variation in risk for Sjögren's syndrome in men (versus 6-fold and 15-fold among women respectively) and affected schizophrenia risk about twice as strongly in men as in women. At a protein level, both C4 and its effector (C3) were present at greater levels in men than women in cerebrospinal fluid ( p <10 -5 for both C4 and C3) and plasma among adults ages 20-50, corresponding to the ages of differential disease vulnerability. Sex differences in complement protein levels may help explain the larger effects of C4 alleles in men, women's greater risk of SLE and Sjogren's, and men's greater vulnerability in schizophrenia. Conclusion: These results nominate the complement system as a source of sexual dimorphism in vulnerability to diverse illnesses. References: [1]Hanscombe KB, Morris DL, Noble JA et al. Hum Mol Genet . 2018; 27(21): 3813-3824. [2]Sekar A, Bialas AR, de Rivera H et al. Nature. 2016; 530(7589): 177-83. Acknowledgments: This work was supported by the National Human Genome Research Institute (HG006855), the National Institute of Mental Health (MH112491, MH105641, MH105653), and the Stanley Center for Psychiatric Research. The KCL/GSTT biomedical research centre. Disclosure of Interests: Nolan Kamitaki: None declared, Bob Handsaker: None declared, David Morris: None declared, Carl Langefeld: None declared, Robert Graham Employee of: Genentech, Speakers bureau: Genentech, Lindsey Criswell: None declared, Steve McCarroll: None declared, Tim Vyse: None declared